Challenging the decision of the financial commissioner in court: distribution of the burden of proof - Egorova, Olga (SHS web of conferences, 2022)
This article discusses evidentiary activities with an insurance (financial) company contesting the decision of the financial commissioner, adopted by him at the request of a consumer of financial services at the pretrial stage of resolving an auto insurance conflict. Comparative legal analysis, system-structural analysis, and synthesis make up the methodological basis of the study. The relevance of the study, because of the legal nature of cases challenging the decision of the financial commissioner, reflecting a qualitatively “new” format of the mechanism for protecting the rights of this participant in auto insurance legal relations in the Russian Federation, is because proving in any civil case makes up the “core” of all judicial activities to resolve civil law conflict. The author evaluates implementing the legally established paradigm of adversarial litigation in the consideration and resolution of this category of cases, because the subject of judicial review is the decision of a public competent person, who, as a general rule, is charged with proving the legality and validity of his decision. The article explores the feasibility of implementing an “active” role of the court in implementing this mechanism for protecting the rights of insurance companies.